Constructing Positive Peace: A Critical Discourse Analysis of Prabowo's 2025 UNGA Speech - Muhammad Hasan Syaifurrizal Al-anshori; Bayu Setiawan; Bambang Wahyudi; Nefra Firdaus; Arifuddin Uksan (Aksaqila International Humanities and Social Sciences [AIHSS] Journal, 2026)
This study examines the construction of positive peace narratives in President Prabowo Subianto's speech delivered at the 80th Session of the United Nations General Assembly (UNGA) in 2025. The study employed a qualitative approach using Norman Fairclough's Critical Discourse Analysis (CDA), combined with Johan Galtung's theory of Positive Peace as the analytical framework. The primary data consisted of the official transcript of the speech, supported by government documents and media reports. The findings revealed that the speech constructed peace not merely as the absence of armed conflict but as the presence of justice, equality, humanitarian protection, and effective multilateral cooperation. Six dominant themes emerged from the analysis: justice and equality, humanitarian concerns, international cooperation, multilateralism, peacebuilding, and structural violence. The speech also positioned Indonesia as an active middle power and a norm entrepreneur committed to promoting a just and rules-based international order. Through its discursive strategies, the speech reinforced Indonesia's identity as a peace-promoting state and demonstrated how political discourse can contribute to the construction of global peace narratives and international legitimacy.